The Hypothetic OMIRE Learning Model to Improve The Scientific Literacy of Prospective Science Teachers - Sarini, Putri; Widodo, Wahono; Sutoyo, Suyatno; Suardana, I Nyoman (Indonesia Emerging Literacy Education, 2024)
Objective: Prospective science teachers must have good scientific literacy skills as critical agents in developing future generations' scientific literacy. However, the scientific literacy skills of prospective science teachers in Indonesia still need to improve. This research tries to formulate the OMIRE learning model to increase the scientific literacy of prospective science teachers. Method: The method used is a literature study with a qualitative research type. Results: The hypothetical OMIRE learning model synthesizes inquiry-based learning models and culture-based learning models to develop the scientific literacy of prospective science teachers. This model is based on several learning theories, including constructivism, Piaget's cognitive development theory, Vygotsky's social constructivist theory, Ausuble's meaningful learning, Bruner's discovery learning, Novak's concept map (mind map), information processing theory, collateral learning theory, boundary crossing metaphor culture, and scientific reconstruction. The hypothetical OMIRE learning model consists of five phases: Observation (O), Mind Mapping (M), Investigation (I), Reconstruction (R), and Evaluation (E). Novelty: The hypothetical OMIRE learning model can develop the scientific literacy of prospective science teachers. Further research needs to be conducted to test the validity, practicality, and effectiveness of the OMIRE learning model in improving the scientific literacy of prospective science teachers.